Reply: Dupuytren's Disease Predicts Increased All-Cause and Cancer-Specific Mortality. Issue 5 (May 2021) - Kuo, Rachel Y. L.; Ng, Michael; Prieto-Alhambra, Daniel; Furniss, Dominic
Abstract : Supplemental Digital Content is available in the text.